From repair costs and casualties to human displacements in the aftermath of an earthquake. The case of buildings with and without pre-existing damage exposed to a Mw 7.1 scenario in the Messina Strait, Italy - J. Camilo Gomez-Zapata; Cecilia I. Nievas; Graeme Weatherill; Fabrice Cotton (Geomatics, Natural Hazards & Risk)
In seismic risk assessment, expert-elicited collapse factors are used to estimate casualties (injuries and fatalities). However, these approaches often overlook buildings’ pre-existing (pre-earthquake) deterioration. Recent methods estimate human displacement by assuming that occupants of extensively or completely damaged buildings become homeless, without first assessing fatalities, injury levels, and unharmed populations probabilistically. This study presents a method for assessing human displacement that incorporates multi-severity casualty estimates alongside the updated residential capacity of serviceable buildings. It shows that pre-existing damage, represented by hypothetical global damage grades as a proof of concept, can influence casualty estimates and displacement outcomes following an earthquake. The method is applied to exposed buildings and populations in Eastern Sicily and Southern Calabria, Italy. These are spatially aggregated into high-resolution geocells and subjected to hundreds of ground motion fields under a Mw 7.1 earthquake scenario in the Messina Strait, similar to the 1908 event that caused extensive damage and loss of life. For each simulation, damages, non-economic losses (human-centred risk metrics), and economic losses (repair costs) are computed, including costs for portfolios with and without depreciation based on their deterioration levels. This framework aids disaster risk reduction by assessing human displacement and shows the need for emergency shelter facilities.